THE EFFECT OF DIFFERENT KINEMATIC PATHWAYS, ACCORDING TO AN AUXILIARY APPARATUS, IN THE DEVELOPMENT OF CLEAN AND JERK LEARNING BY WEIGHTLIFTING FOR BUDDING LIFTERS - Ali Lateef, Nibras; Khaleel Khamees, Majid (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to use the factory assistive educational system with the aim of improving the motor path and developing performance to raise the clean & jerk for juniors and overcome the factor of fear and confusion during the performance of dropping the weight and the research problem lies in the fact that most athletes care about physical strength or exercises that increase muscle strength and do not pay attention to exercises that The proper performance that enables the quadruple to perform greater lift and achieve higher performance than it achieved, and in some cases the lifters or coaches forget the importance of dynamic performance and ignore its importance in athletic achievement and accuracy of technique, just as the fear factor controls them. The study aimed to identify the performance development of the lifting clean & jerk to fully identify the differences between the pre- and post-tests of the motor path. The researcher assessed the experimental approach’s suitability to the nature of the research problem. The research community was identified by emerging weightlifting players and the sample was chosen intentionally by a group of young players belonging to the Diyala Sports Club who practice their training on the club halls and they are the most committed and like the research sample by (6) players for the experimental group and (6) Players for the control group, as the researchers conducted the kinematic analysis of the control and experimental groups in the pre-test in the high clean & jerk, and the researchers manufactured an auxiliary device that improves the kinematic path of the clean & jerk lift and supports regular and semi-regular exercises, then the post-test was done for the control groups and Experimental. In light of the findings of the researchers, they concluded my machines. There is a clear superiority of the experimental group that used the auxiliary device; the auxiliary device prepared has an effective effect in developing and improving players’ learning of high clean & jerk performance, and the apparatus has an effective impact in reducing errors during learning and training on the performance of high clean & jerk.